Clinical evaluation of bulk-fill and universal nanocomposites in class II cavities: five-year results of a randomized clinical split-mouth trial - Schoilew, Kyrill; Fazeli, Shila Marlen; Felten, Anna; Sekundo, Caroline; Wolff, Diana; Frese, Cornelia (Journal of dentistry, 2023)
Aim - Evaluating the clinical survival and quality parameters of class-II restorations using 3M™ FiltekTM Bulk Fill Posterior Restorative compared to 3M™ FiltekTM Supreme XTE Universal Restorative over a period of five years. - Materials and methods - A longitudinal, randomized, prospective split-mouth study with 60 patients (29 female, 31 male; mean age 44 y; range 20-77 y) and a total of 120 load-bearing class II restorations (TEST: n=60 Filtek Bulk Fill Posterior Restorative; CONTROL: n=60 Filtek Supreme XTE Universal Restorative) was conducted. Clinical evaluation was performed by blinded evaluators according to FDI criteria. Kaplan-Meier method was used for survival analysis and an intergroup comparison (Mann-Whitney-U-Test) was carried out. A basic significance level of 0.05 was corrected by the Bonferroni method to account for multiple testing (significance after correction: p<0.00067). - Results - The mean overall survival of restorations was 92% after 56.98±1.51 months in the TEST group (95 CI= 54.02;59.94) and 92% after 57.25±1.46 months (95 CI= 54.39; 60.12) in the CONTROL group (log-rank p=0.995). In total, four failures occurred in both TEST and CONTROL group during the observation period (mean annual failure rate: 1.6%). The most common reasons for failure were chipping-fractures, debonding, cracked-tooth-syndrome and recurrent decay. With regard to the FDI criteria, no significant differences between TEST and CONTROL material occurred for any of the evaluated variables. In the TEST group two restorations had to be repaired and two had to be replaced, in the CONTROL group four restorations had to be replaced. - Conclusion - Both materials showed acceptable clinical performance and survival during the 5-year observation period. - Clinical Significance - The use of a nanofilled bulk-fill composite proved to be an aesthetically, functionally and biologically satisfactory alternative in posterior dentition.